Estimating occupancy of Chinese pangolin (Manis pentadactyla) in a protected and non‐protected area of Nepal. Issue 10 (17th March 2020) - Sharma, Sandhya; Sharma, Hari P.; Chaulagain, Chanda; Katuwal, Hem B.; Belant, Jerrold L.
Abstract: Chinese pangolin is the world's most heavily trafficked small mammal for luxury food and traditional medicine. Although their populations are declining worldwide, it is difficult to monitor their population status because of its rarity and nocturnal behavior. We used site occupancy (presence/absence) sampling of pangolin sign (i.e., active burrows) in a protected (Gaurishankar Conservation Area) and non‐protected area (Ramechhap District) of central Nepal with multiple environmental covariates to understand factors that may influence occupancy of Chinese pangolin. The average Chinese pangolin occupancy and detection probabilities were Ψ ^  ±  SE  = 0.77 ± 0.08; p ^  ±  SE  = 0.27 ± 0.05, respectively. The detection probabilities of Chinese pangolin were higher in PA ( p ^  ±  SE  = 0.33 ± 0.03) than compared to non‐PA ( p ^  ±  SE  = 0.25 ± 0.04). The most important covariates for Chinese pangolin detectability were red soil (97%), food source (97.6%), distance to road (97.9%), and protected area (97%) and with respect to occupancy was elevation (97.9%). We recommended use of remote cameras and potentially GPS collar surveys to further investigate habitat use and site occupancy at regular intervals to provide more reliable conservation assessments. Abstract : Chinese Pangolin detection probabilities is higher in protected areas than non‐protected area.